Medical conditions at enrollment do not impact efficacy and safety of the adjuvanted recombinant zoster vaccine: a pooled post-hoc analysis of two parallel randomized trials - Oostvogels, Lidia; Heineman, Thomas C; Johnson, Robert W; Levin, Myron J; McElhaney, Janet E; Van den Steen, Peter; Zahaf, Toufik; Dagnew, Alemnew F; Chlibek, Roman; Diez-Domingo, Javier; Gorfinkel, Iris S; Hervé, Caroline; et al. (Human vaccines & immunotherapeutics, 2019)
In two pivotal efficacy studies (ZOE-50; ZOE-70), the adjuvanted recombinant zoster vaccine (RZV) demonstrated >90% efficacy against herpes zoster (HZ).Adults aged ≥50 or ≥70 years (ZOE-50 [NCT01165177]; ZOE-70 [NCT01165229]) were randomized to receive 2 doses of RZV or placebo 2 months apart. Vaccine efficacy and safety were evaluated post-hoc in the pooled (ZOE-50/70) population according to the number and type of selected medical conditions present at enrollment.At enrollment, 82.3% of RZV and 82.7% of placebo recipients reported ≥1 of the 15 selected medical conditions. Efficacy against HZ ranged from 84.5% (95% Confidence Interval [CI]: 46.4-97.1) in participants with respiratory disorders to 97.0% (95%CI: 82.3-99.9) in those with coronary heart disease. Moreover, efficacy remained >90% irrespective of the number of selected medical conditions reported by a participant.As indicated by the similarity of the point estimates, this post-hoc analysis suggests that RZV efficacy remains high in all selected medical conditions, as well as with increasing number of medical conditions. No safety concern was identified by the type or number of medical conditions present at enrollment.
Keywords: interpretace statistických dat; rizikové faktory; Chronic Disease; Data Interpretation, Statistical; chronická nemoc; senioři; Vaccines, Synthetic; syntetické vakcíny; Male; Female; Comorbidity; Aged; Middle Aged; Vaccine Potency; postherpetická neuralgie; Herpes Zoster; potence vakcíny; Vaccination; herpes zoster; mužské pohlaví; vakcína proti pásovému oparu; ženské pohlaví; Adjuvants, Immunologic; Risk Factors; adjuvancia imunologická; komorbidita; vakcinace; Herpes Zoster Vaccine; Immunocompromised Host; Neuralgia, Postherpetic; lidé středního věku; imunokompromitovaný pacient; lidé; Humans